The Diversity of Molluscs (Gastropods and Bivalves) in Wabula Waters, Buton Regency, Southeast Sulawesi: Indonesia - Haydar, Haydar Ali Yahya; Pringgenies, Delianis; Wijayanti, Diah P. (Jurnal Moluska Indonesia, 2024)
Gatropods and Bivalvia class mollusks can be found in both freshwater and marine environments. Mollusks from the Gastropod and Bivalvia classes that live in the sea are often found in the intertidal to subtidal zones. Wabula is one of the coastal areas on Buton Island. The waters of Wabula are used as a tourism site, traditional site, and also as a conservation area for fisheries resources. Information regarding the diversity of mollusks in Wabula waters is still limited. This research aims to determine the diversity of mollusk species in the Gastropod and Bivalvia classes in Wabula waters through the analysis of density, diversity, and dominance indices. This research uses quadrant transects measuring 1 x 1 meters. The research was carried out at three stations: Station I on the coast, Station II in seagrass beds, and Station III in the coral reef ecosystem. The composition of the mollusks from the Gastropod and Bivalvia classes found was 158 individuals, consisting of 20 species from the Gastropod class and 3 species from the Bivalvia class. The most commonly found mollusk genera are Rhinoclavis vertagus and Nerita histrio. The ecological index values ​​obtained are density ranging from 10.3-28 Indiv/; diversity (H') 1.44-1.77; uniformity (E) 0.73-0.90; and dominant (D) 0.19-0.34.